Seaweed farming in Zanzibar - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Earnings from seaweed farming in Zanzibar are exceeding those from fishing and are higher than the minimum wage in Tanzania. Thousands of villagers are now actively farming seaweed and annual production is said to be about 500 tonnes. Interest in...